TP53 mutations predict sensitivity to adjuvant gemcitabine in patients with pancreatic ductal adenocarcinoma: next-generation sequencing results from the CONKO-001 trial - Sinn, Marianne; Sinn, Bruno V.; Treue, Denise; Keilholz, Ulrich; Damm, Frederik; Schmuck, Rosa; Lohneis, Philipp; Klauschen, Frederick; Striefler, Jana K.; Bahra, Marcus; Bläker, Hendrik; Bischoff, Sven; et al. (Clinical cancer research, 2020)
Purpose: We performed next-generation sequencing (NGS) in the CONKO-001 phase III trial to identify clinically relevant prognostic and predictive mutations and conducted a functional validation in The Cancer Genome Atlas (TCGA) sequencing data. - Experimental Design: Patients of the CONKO-001 trial received curatively intended surgery for pancreatic adenocarcinoma (PDAC) followed by adjuvant chemotherapy with gemcitabine (Gem) or observation only (Obs). Tissue samples of 101 patients were evaluated by NGS of 37 genes. Cox proportional hazard models were applied for survival analysis. In addition, functional genomic analyses were performed in an NGS and RNA-sequencing dataset of 146 pancreatic tumors from TCGA. - Results: The most common mutations in the CONKO cohort were KRAS (75%), TP53 (60%), SMAD4 (10%), CDKNA2 (9%), as well as SWI/SNF (12%) complex alterations. In untreated patients, TP53 mutations were a negative prognostic factor for disease-free survival (DFS; HR mut vs. WT 2.434, P = 0.005). With respect to gemcitabine treatment, TP53 mutations were a positive predictive factor for gemcitabine efficacy [TP53mut: HR for DFS Gem vs. Obs, 0.235 (0.130 - 0.423; P < 0.001); TP53wt: HR for DFS Gem vs. Obs, 0.794 (0.417 - 1.513; P = 0.483)] with a significant test for interaction (P = 0.003). In the TCGA dataset, TP53 mutations were associated with shortened DFS. - Conclusions: In CONKO-001, the benefit from adjuvant gemcitabine was confined to the TP53mut patient group. This potentially clinical relevant observation needs to be confirmed in independent prospective studies. The sensitivity of TP53mut PDAC to gemcitabine in CONKO-001 provides a lead for further mechanistic investigations.
Gesehen am 07.09.2020